Involvement of phosphatidylserine externalization in the down-regulation of c-myb expression in differentiating C2C12 cells - Kašpar, Petr; Dvořák, Michal (Differentiation, 2008)
Analysis of c-myb gene down-regulation in differentiating C212 cells revealed that in proliferating cells, c-myb expression is high and ceases as the proliferation rate decreases. However, a low level of c-myb mRNA was detected in confluent non-proliferating differentiating cells for an extended period of time before it declined to an undetectable level. The time course of c-myb gene silencing in differentiating cells correlated with exposition of phosphatidylserine (PS) on the cell surface. Moreover, the interaction of exposed PS with exogenously added annexin V perturbed PS-mediated cell signaling and transiently up-regulated the declining c-myb expression. We, therefore, suggest that cell surface-exposed PS, which plays a role in the process of myotube formation, is also involved in the down-regulation of c-myb expression.
Keywords: Annexin A5; buněčná diferenciace; Financing, Organized; Fluorescent Antibody Technique; Cell Differentiation; polymerázová řetězová reakce s reverzní transkripcí; annexin A5; RNA, Messenger; sekvence nukleotidů; Proto-Oncogene Proteins c-myb; Reverse Transcriptase Polymerase Chain Reaction; financování organizované; zvířata; protoonkogenní proteiny c-myb; Animals; myši; fluorescenční protilátková technika; Cell Line; Phosphatidylserines; DNA Primers; messenger RNA; Base Sequence; Mice; fosfatidylseriny; buněčné linie; DNA primery